PENENTUAN KUALITAS AUDIT BERDASARKAN UKURAN KANTOR AKUNTAN PUBLIK DAN BIAYA AUDIT - BERTY WAHYU PUTRI (Universitas Katolik Widya Mandala Surabaya, 2012)
Audit quality is the probability of where an auditor discovered and reported on the existence of a breach in the accounting system auditenya. As a proxy for audit quality, the CPA firm size is frequently associated with the company's reputation. In this case, the reputation associated with its clients and resources, both human resources and wealth (assets). So that his reputation has also been considered both by the people and causes they will conduct an audit to be more careful. On the other hand, audit fees as a proxy for audit quality will depend on several factors in audit engagement, namely: financial of clients, the size of its client’s company, CPA firm size, expertise of the auditor of the industry, and the efficiency of the technology owned by the auditor. Larger audit firm are likely to cost higher fees. In this case, the premium fee which earned by a larger CPA firm size, such as The Big Four, is on 20% higher than a small CPA firm size. Many studies have shown empirical evidence that these two proxies, Firm size and audit fees, has delivered a quality audit. On one hand, a larger CPA firm size is likely will result in a higher quality audit than a small CPA firms size. This is because a larger CPA firm size has the resources of the more experienced and more loyal to his work. On the other hand, a higher audit fees is also tend to produce higher quality audit results as well. This may be caused due to the high quality of the auditor who owned by larger CPA firm size in auditing activities. As result, a high quality auditor who owned by larger CPA firm size has resulted in the higher perception of ability and experience of auditing as well. Furthermore, as larger CPA firm size has allocated more funds for their auditors, the auditors also have the ability to improve the quality of their performance.